Feasibility of proton transmission-beam stereotactic ablative radiotherapy versus photon stereotactic ablative radiotherapy for lung tumors: a dosimetric and feasibility study. - Benjamin Mou (Public Library of Science (PLoS), 2014)
Stereotactic ablative radiotherapy is being increasingly adopted in the treatment of lung tumors. The use of proton beam therapy can further reduce dose to normal structures. However, uncertainty exists in proton-based treatment plans, including range uncertainties, large sensitivity to position uncertainty, and calculation of dose deposition in heterogeneous areas. This study investigated the feasibility of proton transmission beams, i.e. without the Bragg peak, to treat lung tumors with stereotactic ablative radiotherapy. We compared three representative treatment plans using proton transmission beams versus conformal static-gantry photon beams. It was found that proton treatment plans using transmission beams passing through the patient were feasible and demonstrated lower dose to normal structures and markedly reduced treatment times than photon plans. This is the first study to demonstrate the feasibility of proton-based stereotactic ablative radiotherapy planning for lung tumors using proton transmission beams alone. Further research using this novel approach for proton-based planning is warranted.